THE ROLE OF PUBLIC PRIVATE PARTNERSHIP IN DEVELOPING CATASTROPHE INSURANCE MARKET - Darko Blazhevski (Economic Review)
Natural and man made disasters cause severe human, physical and economic damage, both for the economy and for the population. There is a widespread perception that property insurance is the most efficient and economical way to protect against financial losses caused by natural disasters. Regardless of this fact, in many countries in the world, insurance against natural disasters is poorly developed, both on the supply side and on the demand side. The analysed trends in the coverage of damage from catastrophic risks on a global level in the period from 2000 to 2016 show that on average only 28.8% of the total damages were covered. Effective strategies for financing catastrophic risks must be tailored to the needs and capabilities of each country. For these reasons, the paper analyses various world experiences, taking into account countries with different degrees of development and systems (Australia, Austria, the UK, the Caribbean, China, Romania, Russia, the USA, Spain, France, Turkey and Romania). A special survey was conducted in North Macedonia, which was taken as a case study. The conclusions suggest that the insurance of catastrophic risks should be organized as compulsory insurance for households in urban areas. Regarding the risks, we consider that compulsory insurance should cover earthquake and flood, although at the individual level the consequences of the flood affect a relatively smaller population coverage. Making a legally binding solution must be well thought out in the segment of law enforcement. Regarding the operational aspects of implementing a legally binding solution, the principles of insurance should be used, and the world practice indicates that it is possible only with the involvement of the insurance companies.